Novel biallelic TRNT1 mutations lead to atypical SIFD and multiple immune defects - Lu Yang; Xiuhong Xue; Ting Zeng; Xuemei Chen; Qin Zhao; Xuemei Tang; Jun Yang; Yunfei An; Xiaodong Zhao (Genes and Diseases, 2020)
Mutations in the gene encoding transfer RNA (tRNA) nucleotidyltransferase, CCA-adding 1 (TRNT1), an enzyme essential for the synthesis of the 3′-terminal CCA sequence in tRNA molecules, are associated with a rare syndrome of congenital sideroblastic anemia, B cell immunodeficiency, periodic fevers, and developmental delay (SIFD). Clinical manifestations and immunological phenotypes were assessed in a Chinese patient with novel compound heterozygous mutations in TRNT1. The patient required multiple hospitalizations starting at the age of 2 years for recurrent fevers without an infective cause. During the febrile episode, the patient was found to have microcytic hypochromic anemia, B cell lymphopenia, and hypogammaglobulinemia. Targeted gene sequencing identified novel compound heterozygous mutations in the TRNT1 gene (c.525delT, p.Leu176X; c.938T>C, p.Leu313Ser). Immunophenotyping revealed increased CD8+ T cells, CD4+ terminally differentiated effector memory helper T lymphocytes (CD4 TEMRA), and CD4+ effector memory lymphocytes (CD4 EM). Analysis of CD4+ T subsets identified decreased T follicular helper cells (Tfh) with a biased phenotype to Th2-like cells. The patient also showed a lower percentage of switched memory B (smB) cells. Additionally, defects in the cytotoxicity of the patient's NK and γδT cells were shown by CD107alpha expression. In conclusion, TRNT1 mutations may lead to multiple immune abnormality especially humoral and cytotoxicity defects, which indicate that SIFD is not only suffered ‘Predominantly antibody deficiencies’ in IUIS classification system, and further studies are needed to understand the pathogenesis of immunodeficiency in these patients. Keywords: Mild phenotype, Multiple immune defects, Novel mutations, SIFD, TRNT1